Draft precis of evidence to be given before the Departmental Committee on Midwives
1928-09 1928 1920s 6 pages 3. 9. No doctor should be on the maternity panel under National Health Insurance unless he or she is adequately trained. This affects the midwife for with increasing need of training for the doctor the opportunities of training for the midwife may be more difficult to arrange. We think it essential that every medical school should extend its training facilities and while the free provision of doctors will tend to lessen the number of women on the outdoor district of any medical school or any hospital which has also a medical school, we believe that better ante-natal care will increase the numbers within the hospitals. It is very important that hospitals approved as medical schools giving maternity teaching should not be allowed to exclude women students as it is an undoubted fact that women prefer to go for ante-natal advice to a woman doctor, and it is likely that women doctors will qualify in increasingly great numbers for midwifery practice. If there is to be any discrimination in Medical Schools, it should rather be in favour of women rather than men students. 10. There has been considerable fear expressed, especially by those with experience of well-trained midwives, lest unskilled, old-fashioned and careless doctors should replace well-trained experienced midwives as the responsible attendants at childbirth. It is unfortunately true that there are to-day some doctors who are insufficiently qualified for such work and are yet doing it. It has however to be admitted that the standard of medical practice has been greatly raised in general work since the establishment of National Health Insurance. This is mainly because:- (1) The doctor has a better opportunity of preventive work. (2) The doctor has a certain economic security which frees his mind of some of the anxiety of the competitive system, fear of bad debts, etc. (3) The doctor is under some supervision and negligence may have very serious results. If attendance at maternity cases becomes part of medical benefit for which the approved society must pay, the doctors on the panel - like those for such specialist work as ophthalmology, must have some special qualification. Their training must have given them sufficient experience. The Benefit should include the patient's coming for ante-natal advice as a necessary part and the doctor must fit himself for that duty. Some supervision would also be involved as in all Insurance work, while there would be additional reason for good work resulting from the inquiry into all maternal deaths. These considerations would make the incapable doctor hesitate to risk his reputation in such cases; he would either fit himself for the work by a refresher course or not seek inclusion on the Panel. At the same time, the opportunity to do good work, the provision of the skilled assistance of a midwife, the development of research and the increase in opportunities for consulting specialists, attending maternity hospitals and refresher courses, would stimulate the good practitioner to further effort. 11. On the other hand, there is a tendency at present to ask the midwife to undertake work, especially in connection with ante-natal examination that is not suitable. The use of a stethoscope, e.g. and still more the use of a measuring instrument is work for which her training to-day certainly does not equip her. Even with the extension we suggest we do not think we can make up for the several years which a medical student spends in theoretical and practical work which does give a wide experience 292/824/1/116